2002
DOI: 10.1002/pen.11041
|View full text |Cite
|
Sign up to set email alerts
|

Mixed matrix membrane materials with glassy polymers. Part 1

Abstract: Mixed matrix materials comprising molecular sieve entities embedded in a polymer matrix can economically increase membrane permselectivity, thereby addressing a key challenge hindering the widespread use of membrane‐based gas separations. Prior work has clarified the importance of proper selection of the dispersed sieve phase and the continuous matrix phase based on their intrinsic transport properties. Proper material selection for the two components, while necessary, is not sufficient since the interfacial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
230
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 364 publications
(240 citation statements)
references
References 11 publications
3
230
0
7
Order By: Relevance
“…Although the model describes ideal transport properties of mixed matrix membranes, it has limitations when non-ideal effects exist like sieve-in-cage, matrix rigidification and stress dilated matrices 7,10 . To account for non-ideal effects one can apply a "nested" version of the Maxwell model.…”
Section: Maxwell Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the model describes ideal transport properties of mixed matrix membranes, it has limitations when non-ideal effects exist like sieve-in-cage, matrix rigidification and stress dilated matrices 7,10 . To account for non-ideal effects one can apply a "nested" version of the Maxwell model.…”
Section: Maxwell Modelmentioning
confidence: 99%
“…For glassy polymers the formation of defect-free membranes can be achieved by the compatibilization of the two phases with silanes as reported in the literature 3,5 . Unfortunately, high performance membranes are more complex to obtain, due to difficulties in avoiding the formation of interfacial defects between the dispersed and continuous matrix phases [6][7][8][9][10] . Zeolitic imidazolate frameworks (ZIFs) [11][12][13] created a new possibility for mixed matrix membranes formation.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have shown that the interfacial region, which is a transition phase between the continuous polymer and dispersed sieve phases, is of particular importance in successful MMM formation [29,34,35].…”
Section: Solid-polymer Mixed-matrix Nanomembranesmentioning
confidence: 99%
“…Therefore, it is highly desirable to provide an alternate cost-effective nanomembrane in a position above the trade-off curves between permeability and selectivity [19]. Mixed-matrix membranes (MMMs) are considered as hybrid membranes containing liquid, solid, or both liquid and solid fillers embedded in a polymer matrix [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. They are densely packed polymer membranes with organic or inorganic nanoparticles introduced into their structure.…”
Section: Concept Of Mixed-matrix Nanomembranesmentioning
confidence: 99%
“…One of these widely used approaches is to perform the casting at temperature above the polymer glass transition or either use a polymer with low glass transition temperature and perform the membrane fabrication close to the polymer glass transition temperature. 26,47,49,54,55 To maximize stress relaxation in this method, the matrix flexibility is maintained during the membrane formation. Thus, a low volatile solvent is the choice, however, such a solvent is difficult to find since the typical solvents used for film casting boil below this temperature.…”
Section: Modification Of the Fillers And Casting Conditionsmentioning
confidence: 99%